Avaliação comportamental e eletrofisiológica do processamento auditivo central em indivíduos com traumatismo cranioencefálico leve pré e pós-treinamento auditivo acusticamente controlado - Buriti, Ana Karina Lima [UNIFESP] (2019)
Objective: To characterize and compare the behavioral and electrophysiological assessments of the central auditory processing in individuals with mild degree of traumatic brain injury, pre, post and after 6 months of acoustically controlled auditory training. Method: The sample was composed of ten individuals between 16 and 64 years after mild traumatic brain injury who underwent behavioral assessment of central auditory processing and electrophysiological assessment of hearing before and after the acomplishment of an acoustically controlled auditory training, which was organized in ten sessions. After concluding the stimulation program, we applied a self-assessment questionnaire. In order to assess the stability of the measurements, the individuals were invited to undergo a new re-assessment six months after the acoustically controlled auditory training. Results: In the behavioral assessment of central auditory processing, we noted changes in all tests, with a higher emphasis on speech in noise (90%), followed by the duration standard (80%). By comparing the pre and post assessments, we noted a statistically significant difference in the speech in noise tests in the left ear, dichotic of alternating disyllables in the right ear, sound localization and Random Gap Detecton Fusion, with better results after the acoustically controlled auditory training. In the electrophysiological assessment, we noted changes in the brain stem in the pre-assessment, besides adequacy in 100% of the individuals for wave III latency and I-III interspike interval on the right. In the assessment of the frequency following response, we noted changes in all waves due to latency delay and/or component absence, mainly for D, E, F and O waves; and after the auditory training, D and E waves on the right. For the cognitive potential, we noted a statistically significant difference for the left P3 amplitude with speech stimulus. Between the pre and post assessments, we noted P300 adequacy in 100% of the individuals on the left ear with tone burst stimulus in the post-assessment. In the self-assessment questionnaire, we noted a higher concentration of responses in a significant improvement for auditory performance aspects in noisy environments, attention and alertness level, as well as self-esteem. Conclusion: The individuals with mild traumatic brain injury show central auditory processing disorder in both behavioral and electrophysiological assessments, which was minimized after the acoustically controlled auditory training.